Effect of deformation rate on post-forming interfacial delamination in polymer laminated sheet metals. Issue 15 (17th November 2020) - Noori, Hadi; Jain, Mukesh; Nielsen, Kent
ABSTRACT: The polymer laminated sheet metal (PLSM) is a class of layered materials which involves a sheet metal substrate, a polymer film and an adhesive layer between them. The PLSMs can be potentially used for sheet forming applications. Due to the incompatibility in mechanical and physical properties of the constituents, deformation of the PLSM could cause interfacial delamination between the metallic substrate and polymer adherends. This paper deals with the assessment of the effect of uniaxial elongation rate on post-forming interfacial delamination in PLSMs. For the polymer adherends used in this study, it is concluded that for large strains, higher deformation rate results in less amount of delamination. This behavior is attributed to the time-dependency of mechanical properties of the polymer adherend material. Abbreviations : PLSM: polymer laminated sheet metal; PSA: pressure-sensitive adhesive; BA: bright annealed; PE: polyethylene; PP: polypropylene; PVC: polyvinyl chloride